1976
DOI: 10.1104/pp.57.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Stem Sensitivity and Ethylene Involvement in Phototropism of Mung Bean

Abstract: A system is described for the examination of phototropism in the epicotyl of a dicot seedling, mung bean (Phaseolus aureus Roxb.), under conditions approximating nature, including the use of intact, nonetiolated plants exposed to elevated, continuous, white, unilateral light. It is found that in this system perception of the phototropic stimulus by the leaves alone cannot account for the curvature, and that exposure of the stem is also necessary. The phototropic response was found to be strongly altered in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…4) are in agreement with those of other dicot seedlings (2,8,11). These data support the conclusion that the hypocotyl itself contains the photoreceptor for its positive phototropic curvature in unilateral light since this response did not depend on directional information from the cotyledons, on their being in light or on any immediate supplies from them.…”
Section: Resultssupporting
confidence: 79%
“…4) are in agreement with those of other dicot seedlings (2,8,11). These data support the conclusion that the hypocotyl itself contains the photoreceptor for its positive phototropic curvature in unilateral light since this response did not depend on directional information from the cotyledons, on their being in light or on any immediate supplies from them.…”
Section: Resultssupporting
confidence: 79%
“…The removal ofthe leaves ofgreen sunflower seedlings suppressed the phototropic responsiveness by more than half (Shibaoka and Yamaki, 1959). When one of the primary leaves ofuniformly illuminated mung bean plants was masked, no measurable curvature of the epicotyl occurred, and the masking of both of the primary leaves only reduced the curvature of plants exposed to unilateral light by 25% (Brennan et al, 1976). However, the removal of either one or both of the primary leaves did prevent a phototropic response to the mung bean epicotyl.…”
mentioning
confidence: 93%
“…Removal of the shoot apex and immature leaves of the apical bud of Se/aginella had no effect upon the positive phototropic response ofthe horizontal stems. With mung bean (Phaseo/us aureus), masking the stem tip with an inert lanolin paste containing charcoal reduced the phototropic curvature of the stem by more than half and removal of the tip completely inhibited phototropic curvature (Brennan, Gunckel and Frenkel, 1976). On the other hand, removal of shoot apex had no effect upon the phototropic response of sunflower (Helianthus) hypocotyls (Bruinsma et al, 1975).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For dicotyledons this issue remains unclear, with some controversy in the literature. Although early research suggested that in dicotyledon species the phototropic stimulus is perceived primarily by the leaves and cotyledons (Shibaoka & Yamaki 1959; Lam & Leopold 1966), subsequent studies on de‐etiolated mung bean, cucumber and sunflower seedlings indicated that the primary zone of phototropic perception is the stem (Brennan, Gunckel & Frenkel 1976; Shuttleworth & Black 1977).…”
Section: Introductionmentioning
confidence: 99%